The Effect of Self-Regulated Learning on Student Learning Outcomes Through Religiosity as a Mediating Variable - Muh. Alwi; Risnashari; Sitti Wahidah Masnani (Indonesian Journal Publisher, 2025)
This study aims to investigate the effect of self-regulated learning on student learning outcomes, with religiosity as a mediating variable. The focus of this study is to understand whether religiosity can be an intermediary in the relationship between self-regulated learning and learning outcomes in students of the Basic Education Program at the Open University of Makassar. Using a quantitative approach with a cross-sectional survey design, this study involved 400 students from the Basic Education Program at the Open University of Makassar. The research variables consisted of self-regulated learning (8 items), religiosity (5 items), and learning outcomes (6 items), which were measured using a Likert scale. The data were analyzed using Smart PLS version 4.0 software. The results of the analysis showed that religiosity had a significant effect on learning outcomes (β = 0.557, p-value = 0.000), with an R² value of 0.319. However, self-regulated learning did not show a significant direct effect on learning outcomes (β = 0.053, p-value = 0.246). Self-regulated learning had a significant effect on religiosity (β = 0.110, p-value = 0.033), and religiosity acted as a mediator between self-regulated learning and learning outcomes, with a significant indirect effect (β = 0.061, p-value = 0.033). These findings indicate that religiosity plays an important role in improving student learning outcomes, both directly and through its role as a mediator between self-regulated learning and learning outcomes. Keywords: Self-Regulation Learning; Learning Outcomes; Religiosity; Mediation.